The effectiveness of bilingual school programs for immigrant children - Berlin Arbeitsstelle Interkulturelle Konflikte und Gesellschaftliche Integration (AKI) (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2005)
Is bilingual education a promising and effective type of instruction conducive to enhancing the academic achievement of immigrant children? This question was the subject of the workshop “The Effectiveness of Bilingual School Programs for Immigrant Children” or-ganized by the Programme on Intercultural Conflicts and Societal Integration (AKI) at the Social Science Research Center Berlin (WZB). Experts from the United States, the Nether-lands, Sweden and Germany gathered in November 2004 to discuss respective national experiences and evidence on the effects of bilingual education. This volume presents the revised papers.
Keywords: 300